Microbial Infections Associated with Diabetic Foot Ulcer in Nasiriyah City - Muna F. Jahad; Mohammed Hashim AL-Yasiri (Indian Journal of Forensic Medicine & Toxicology, 2021)
Diabetic foot ulcers (DFUs) are a major complication of diabetes lead to development of gangrene associatedwith reduced patient quality of life, lower-extremity amputation, hospitalization, and high morbidity andmortality. This study was aimed to identify the pathogenic microorganisms in diabetic foot ulcers and to testtheir antibiotic susceptibility. A total of 134 patients with diabetic foot ulcers (DFU) attending to Diabeticcenter/ Thi-Qar province, South of Iraq were randomly selected. Samples were cultured for isolating bacteriaspecies and Fungi species. Antibiotic sensitivity testing for bacteria species was done by Kirby Bauer discdiffusion method. Elderly diabetic males were frequently observed to develop foot ulcers higher than female.The most of patients 56 (41.79%) were in the age group 51 to 60 years followed by the 36 (26.86%) patientswere in age group 41 to 50 years. Out of 162 isolates, bacteria species was 116 (71.6%) more than Fungispecies 46 (28.4%). The most isolated bacteria was Proteus mirabilis 25 (15.43%) followed by Enterobactercloacae 22 (13.58%) and both Escherichia coli and Staphylococcus epidermidis 17 (10.49%). Diabetic footinfections are life-threatening. Many pathogens associated with diabetic foot ulcers.